An integrated critical approach to off-fault strike-slip motion triggered by the 2011 Van mainshock (Mw 7.1), Eastern Anatolia (Turkey): New stress field constraints on subcrustal deformation. (September 2021) - Toker, Mustafa; Pınar, Ali; Hoşkan, Nihan
Graphical abstract: Highlights: The Van rupture source generated off-fault aftershocks in the entire crust. Strike-slip aftershocks increased the intensity of stress in an off-fault area. These aftershocks revealed rotational upper/non-rotational lower crust. Strike-slip motion was activated and rooted in subcrustal depths. This study leads to paradigm changes in interpreting subcrustal strike-slip faulting. Abstract: In this study, we retrieved the finite source characteristics of the October 23, 2011 Van earthquake ( Mw 7.1 ) using the teleseismic waveforms to focus on the source location. The outstanding off-fault aftershock sequence of the Van mainshock was readily explained by calculating the Coulomb stress changes imparted to the surrounding crust. This may be accomplished through finite source modelling to examine the stress interaction between the fault, ruptured by the Van mainshock, and the surrounding fault(s) triggered by the same mainshock. In addition, to provide further support for the Coulomb failure stress changes in the off-fault area, centroid moment tensor (CMT) inversion of the off-fault aftershocks was performed and stress tensors were derived from their focal solutions. This identified the dominant fault slip, the constraints of the crustal stress fields and illuminated the crustal nature of the stress interaction. The off-fault aftershocks showed a strike-slip stress regime in rotational (to NW) and non-rotational (to N) stress fields of the upper and lower crusts, respectively. However, this was inconsistent with a horizontal compressional stress direction striking to the north. This suggests that a local source and/or rotation of lateral variation in stress magnitudes in crustal and sub-crustal structures strongly perturbed the regional stress field. It was also evident that these strike-slip aftershocks increased the intensity of stress in an off-fault area, NE of the source rupture. This revealed a uniquely triggered strike-slip motion, activated and rooted in the weak lower crust. We conclude that the Van mainshock rupture source area, associated with the stress changes imparted to the surrounding crust, had undergone anomalous modifications to generate distinctive off-fault aftershock responses in the entire crust, and also triggered and loaded the weak lower crust. We hypothesize that the strike-slip motion, the so called "transfer fault", as a distinctly triggered slip event, was generated or selectively activated by subcrustal ductile processes in the absence of mantle lid beneath the study area. However, local slab fragmentation, tearing and cold mantle beneath the study area lead to paradigm changes in interpreting the strike-slip motion and subcrustal deformation. The presence of a small piece of oceanic lithosphere, consistent with fragmented, torn slab and cold mantle, may be an alternative hypothesis that remains to be tested. The Van earthquake, combined with careful examination of associated off-fault aftershocks, revealed new information about stress field constraints on subcrustal deformation. This investigation also provided insights into an important role of stress interaction, with a newly discovered transfer fault within the off-fault area, which extends through the entire crust beneath Lakes Van and Erçek areas.